Time and the soul : where has all the meaningful time gone-- and can we get it back? - Needleman, Jacob (Berrett-Koehler, 2003)
In Time and the Soul Jacob Needleman uses stories-of a middle-aged psychiatrist going back in time to encounter his younger self; of a mysterious meeting in the Central Asian desert; of the mystic master Hermes Trimegistus; as well as stories from the Bhagavad-Gita, the Bible, and other wisdom traditions-to illuminate the great mystery of time and to help us resolve our increasingly dysfunctional relationship to it. Nearly everyone feels stress and anxiety over what's become known as time poverty. Time management techniques treat these symptoms by making our busyness more efficient, but not the underlying cause. Needleman shows that we can get more out of time by breaking free of our illusions about it. He helps us experience time more purposefully and meaningfully. He provides parables, reflections, and a unique mental exercise to give us a new understanding of time. By transforming the way we understand and experience time, this powerful book gives us the equanimity and perspective we need to make the most of the time we are given. A tranquil heart, Needleman writes, is never defeated by time.